Analysis And Design of File Security System AES (Advanced Encryption Standard) Cryptography Based - Khairul Muttaqin; Jefril Rahmadoni (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2020)
The times has made human needs are increasing, including information needs. Therefore, sending and storing data through electronic media requires a process that is able to guarantee the security and integrity of the data that requires an encoding process. Encryption is the process of changing an original data into confidential data that cannot be read. Meanwhile, the decryption process is a process where the confidential data received will be converted back into the original data. In this case the Advanced Encryption Standard (AES) algorithm is used as the latest cryptographic algorithm standard. The previous algorithm was considered unable to answer the challenges of the development of communication technology very quickly. AES is a cryptographic algorithm using the Rijndael algorithm that can encrypt and decrypt blocks of data over 128 bits with a key length of 128 bits. In this study the application of AES as a file security system is carried out, where the encryption and decryption process is carried out on the file. In testing the system a trial is performed on all files with different file sizes and for the results of the encryption process (ciphertext) in the form of files with the file format with the *.encrypted extension.